Value and its aesthetic elements in Renaissance art (Al-Academy, 2024)
The current research dealt with (value and its aesthetic elements in Renaissance art), by studying value and its aesthetic elements in the drawings of Renaissance artists. The first chapter dealt with the problem of the research, its importance and the need for it, and the goal of the research, which was represented by the following: “Value and its aesthetic elements in Renaissance art,” then concluded. The aforementioned chapter defines the terms that are related to the research title. The second chapter includes a presentation of the theoretical framework and previous studies, and consists of two sections: the first section is the nature of value and its aesthetic elements. The second section: Aesthetic values in Renaissance thought. The third chapter specializes in research procedures: the research community, the research sample, the research methodology, the research tool, and analysis of the sample that included (3) works of art. The fourth chapter ended with the research results, including: Aesthetic and artistic values are values that contain many values of aesthetic elements. Conclusions include: European Renaissance paintings tend towards visual embodiment, but with a different content. Then recommendations and suggestions.